An Estimation of the Effect of Density Changes upon Sea Level Measurement at Syowa Station, Antarctica - Michida, Yutaka; Ogawa, Akihiko; Okano, Hirofumi (1996)
The summer party of the 35th Japanese Antarctic Research Expedition carried out an observa- tion for the vertical profile of temperature and salinity in the vicinity of the sea level station at Syowa Station, Antarctica, by using a Nansen water sampling bottle and a reversing thermometer on January 26, 1994. We estimate the effect of seasonal density changes of the sea water above the pressure gauge upon sea level measurement with the gauge, by comparing the density profile determined by the observation in summer of 1994 and previous ones in winter of 1982. In possibly typical cases, the sea level measured with the pressure gauge at Syowa Station can be about 4cm higher in winter than in summer due to the seasonal density changes, which is about 15% of the amplitude of seasonal sea level variation. Published